A ira do capitão-mor: Marçal Nunes da Costa e o governo do Pará no século XVII (Ágora Journal, 2021)
This article presents partial results of research on the government of Pará, in the 17th century, based on the criticisms of Marçal Nunes da Costa to the usurpation of his jurisdiction and that of other captains majors by the governors and captains generals of the State of Maranhão, as well as conflicts between these agents. The text therefore analyzes the political and administrative dynamics in this constituency, involving, mainly, captains majors of Pará and governors, but also the Chamber of Belém, discussing issues such as: the existence and respect for the rulegements; the delegation of powers and jurisdictions by the kings of Portugal to the colonial administrators; the fragility of the authority of the captains-mores of Pará vis-à-vis private interests and the articulation of local powers, through the Chamber, with the governors and captains generals. The methodology used to support the conclusions presented consisted, basically, in the qualitative analysis of official correspondence of the captains-mores with authorities in Lisbon, of regiments for the governments of Pará and the State of Maranhão, of patent letters and, in the comparison of these sources, with information contained in works reference on local political and administrative history.